Differences In Changes In Anxiety Level Of Students When Compiling Thesis With Green Color Therapy Intervention Compared With Deep Breath Relaxation Therapy: Perbedaan Perubahan Tingkat Kecemasan Pada Mahasiswa Saat Menyusun Skripsi Dengan Intervensi Terapi Warna Hijau Dibandingkan Terapi Relaksasi Napas Dalam - Meydia Windy Utami; Titik Endarwati; Furaida Khasanah (Poltekkes Kemenkes Yogyakarta, 2022)
Final-year students are required to complete a thesis, which can cause students to be prone to experiencing anxiety. One of the non-pharmacological therapies to overcome anxiety is green color therapy. Green color therapy will increase levels of the hormones serotonin and oxytocin and decrease the hormone norepinephrine, which will increase mood and happiness, so that anxiety when writing a thesis will decrease. To find out the differences in changes in anxiety levels in students when compiling their thesis with a green color therapy intervention compared to deep breathing relaxation therapy at the Nursing Department of the Poltekkes Kemenkes Yogyakarta. This type of research is a quasi-experiment with a pre and post-test control group design. The number of respondents was 44, who were selected by total sampling. The number of samples in the intervention group was 22 respondents, and the comparison group had 22 respondents. The research instrument used was an anxiety scale questionnaire. Data analysis used a paired t-test and an independent t-test with a significant level of p<0.05. There were significant differences in anxiety levels in the intervention group and the comparison group before being given treatment (p value = 0.00) and after being given treatment (p value = 0.035). Green color therapy is more effective in reducing the anxiety level of students who are preparing their thesis than deep breathing relaxation therapy. Mahasiswa tingkat akhir dituntut untuk menyelesaikan skripsi yang mana dapat menyebabkan mahasiswa rentan mengalami kecemasan. Salah satu terapi non farmakologis untuk mengatasi kecemasan adalah terapi warna hijau. Terapi warna hijau akan meningkatkan kadar hormon serotonin, oksitosin serta penurunan hormon norepinephrine yang akan meningkatkan suasana hati dan rasa bahagia sehingga kecemasan saat menyusun skripsi akan menurun. Penelitian ini bertujuan untuk mengetahui perbedaan perubahan tingkat kecemasan pada mahasiswa saat menyusun skripsi dengan intervensi terapi warna hijau dibandingkan terapi relaksasi napas dalam di Jurusan Keperawatan Poltekkes Kemenkes Yogyakarta. Jenis penelitian quasy eksperiment dengan Pre and posttest control group design. Jumlah responden sebanyak 44 yang dipilih dengan total sampling. Jumlah sampel kelompok intervensi 22 responden dan kelompok pembanding 22 responden. Instrumen penelitian menggunakan kuesioner skala kecemasan. Analisa data menggunakan uji paired t-test dan uji independent t-test dengan taraf signifikan p<0,05. Hasil penelitian diketahui terdapat perbedaan tingkat kecemasan yang signifikan pada kelompok intervensi dan kelompok pembanding sebelum diberikan perlakuan (p value=0,00) dan sesudah diberikan perlakuan (p value =0,035). Terapi warna hijau lebih efektif untuk menurunkan tingkat kecemasan mahasiswa yang sedang menyusun skripsi dibandingkan terapi relaksasi napas dalam.